2009
DOI: 10.1101/cshperspect.a000034
|View full text |Cite
|
Sign up to set email alerts
|

The NF- B Family of Transcription Factors and Its Regulation

Abstract: Nuclear factor-kB (NF-kB) consists of a family of transcription factors that play critical roles in inflammation, immunity, cell proliferation, differentiation, and survival. Inducible NF-kB activation depends on phosphorylation-induced proteosomal degradation of the inhibitor of NF-kB proteins (IkBs), which retain inactive NF-kB dimers in the cytosol in unstimulated cells. The majority of the diverse signaling pathways that lead to NF-kB activation converge on the IkB kinase (IKK) complex, which is responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
1,985
0
24

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,382 publications
(2,051 citation statements)
references
References 105 publications
42
1,985
0
24
Order By: Relevance
“…Activation of the IKK complex is dependent on the phosphorylation of 2 serine residues in at least one of its subunits (Ser176/180 of IKKa or Ser177/181 of IKKb subunit; ref. 13). Therefore, we evaluated the activation status of the IKKa/b complex by Western blot analysis with a phosphospecific antibody that detects the endogenous levels of IKKa and IKKb only when phosphorylated at Ser176 and Ser180 or Ser177 and Ser181, respectively.…”
Section: Minocycline Blocks Ikba Kinase Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the IKK complex is dependent on the phosphorylation of 2 serine residues in at least one of its subunits (Ser176/180 of IKKa or Ser177/181 of IKKb subunit; ref. 13). Therefore, we evaluated the activation status of the IKKa/b complex by Western blot analysis with a phosphospecific antibody that detects the endogenous levels of IKKa and IKKb only when phosphorylated at Ser176 and Ser180 or Ser177 and Ser181, respectively.…”
Section: Minocycline Blocks Ikba Kinase Activationmentioning
confidence: 99%
“…When stimulated by appropriate extracellular signals, IkBa is phosphorylated by inhibitor of IkB kinase (IKK), which results in proteasome-mediated degradation of IkBa. Then the active complex of NF-kB gets librated and translocates to nucleus to mediate transcription of its target genes (13). IKK complex is activated either through autophosphorylation or via phosphorylation by a series of mitogenactivated kinase kinase kinases (MAP3K) including TGFb-activated kinase-1 (TAK1).…”
Section: Introductionmentioning
confidence: 99%
“…IKK␥ (also known as NEMO), a regulatory subunit of IKK, has been shown to play an essential role in functionally activating catalytic subunits of IKK (5,11,18,26,31,44). Since we found that IKK␤ was functionally associated with Nkx3.2-mediated NF-B activation, we next investigated whether NEMO is also involved in this process.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the detailed mechanism involved in the repression of PP2Aca and PP2Acb transcription, we analyzed the potential binding sites of NF-kB or NF-kB downstream genes [28][29][30] in the 5 0 upstream regions of PP2Aca and PP2Acb by using Genomatix software. 31 In addition to NFkB itself, the potential binding sites of several transcription factors, which have been proven to be the target genes of the NF-kB pathway, were identified ( Figure 5G).…”
Section: Inflammatory Stimuli Repressed Pp2ac Expression In An Nf-kbmentioning
confidence: 99%